Determinants of scholar's participation of OAI: Developing a conceptual framework - Aziz W.A.R.A.B.W. (Regional Inform. Center for Sci. and Technol., 2024)
This paper describes the framework used in a study to formulate the requirements for the design and implementation of a knowledge sharing for project-based education. Green Open Access Information is popular among researchers to access information in sharing their knowledge. The purpose of Green Open Access Information is to make the full text of the peer-reviewed research output of scholars/scientists and their institutions visible, accessible, harvestable, searchable and useable by any potential user to access the information from the Internet. Knowledge sharing is widely recognized that it can promote the competitive ability of scholars and it has been the focus of research for this century. Recently, there has been a growing interest in examining the factors that participation of OAI or knowledge sharing. The OAI has been conceived to support scholars sharing needs in making research projects. The study uses the Framework for knowledge sharing for the approach to investigate the initial requirements. The artifact addressed in the framework - readiness - is highlighted in this paper. Readiness in this work refers to major goal within objective or approaches that are significant to the OAI. This includes the readiness to participate the OAI, willingness to participate in making research articles available on the internet, and the success factors. Using multiple data-gathering techniques, the study identifies the readiness factors that support the plan for participation of the OAI. It outlines the vision statement, goals and objectives needed to define the make research articles available on the internet by the Scholars; the context to participate the OAI by the Knowledge Sharing Community; and the knowledge sharing expressed by the participation of OAI. 2018, Regional Inform. Center for Sci. and Technol.